2020
DOI: 10.3171/2019.11.peds19320
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with conversion of an Ommaya reservoir to a permanent cerebrospinal fluid shunt in preterm posthemorrhagic hydrocephalus

Abstract: OBJECTIVEA considerable percentage of preterm infants with posthemorrhagic hydrocephalus initially managed with an Ommaya reservoir require a permanent CSF shunt. The objective of the study was to analyze possible risk factors associated with the need for converting an Ommaya reservoir to a permanent shunt.METHODSThe authors retrospectively reviewed the clinical records of premature infants weighing 1500 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Reducing the number of patients who need permanent CSF diversion may potentially decrease the amount of shunt complications, the incidence of poor neurological outcomes and overall health-care costs. [27][28][29] In our study, 25% of the IVH patients ultimately underwent permanent hydrocephalus shunt surgery, and this finding is basically consistent with previous literature reports. The early removal of conventional EVD followed by the use of an Ommaya reservoir for CSF drainage likely reduces the need for a permanent VP shunt.…”
Section: Discussionsupporting
confidence: 92%
“…Reducing the number of patients who need permanent CSF diversion may potentially decrease the amount of shunt complications, the incidence of poor neurological outcomes and overall health-care costs. [27][28][29] In our study, 25% of the IVH patients ultimately underwent permanent hydrocephalus shunt surgery, and this finding is basically consistent with previous literature reports. The early removal of conventional EVD followed by the use of an Ommaya reservoir for CSF drainage likely reduces the need for a permanent VP shunt.…”
Section: Discussionsupporting
confidence: 92%
“…Only one study that reported on VSGS mentioned labs, only that they were sent prior to VPS insertion [10]. For VADs, three studies explicitly stated that labs were sent after every aspiration [6, 11, 12], one study stated that “clinical investigations followed the punctures” [13], three studies from two research groups merely stated that labs were done “routinely” [14-16], one study “three times per week” [17], one study “at least once a week” [18], two studies “weekly” [19, 20], one study “at 5- to 8-day intervals” [21], and one study just that labs were sent [22].…”
Section: Resultsmentioning
confidence: 99%